Methodology of communicative behaviour experimental study of preschool children with mental retardation - Mityashkina Irina Sergeevna (Studia Humanitatis)
The paper examines the methods of communicative behaviour experimental study of preschool children with mental retardation. The focus is on the specifics of the interaction of such children, analysing both verbal and non-verbal aspects of their communication. Significant data that allow us to assess the level of communicative behaviour and identify the main difficulties faced by children with this nosology were obtained based on the results of the experimental study. The presented results not only enrich the existing knowledge in the field of psychology and pedagogy, but also open up new horizons for the development of effective diagnostic methods and the construction of further correctional work with this group of children.